Investigating The Problems Faced by Nursing Students in Second Language Communicative Skill for Indonesian Vocational Higher Education Mobile Learning - Baharuddin K; Muh Basri; Rahmatia Rahmatia (Pascasarjana Universitas Negeri Makassar, 2021)
The present study focuses on the problems faced by the sixth-semester students of Nursing Study Program at Health Polytechnic of Makassar in Speaking English. It uses a descriptive method to describe the students’ spoken problems which lie in language elements, psychological factors, and learning situation. The subject of the study is taken using cluster random sampling technique. This study uses two kinds of instrument, namely questionnaire and interview. Both are used to identify and to find out the problems faced by the students in speaking English. The findings of the study show the students’ obstacles in speaking English, namely: the lack of grammar understanding (68%) the lack of confidence (62%), the infrequent practice (58%), the lack of vocabulary (50%), the low motivation (46%), the anxiety (44%), the influence of classroom interaction (44%), the low listening skill (40%), the lack of knowledge and interest (32%), the influence of mother tongue or local language (28%), the impact of formal events (28%), the lack of pronunciation (24%) and the inappropriate topic talk(16%). Thus, it is implied that the problems faced by the students in speaking English need serious attention for the teachers of English to conduct an effective teaching method to help encourage the students to speak English.